Low velocity failure and integrity assessment of foam core sandwich panels (Fracture and Structural Integrity, 2019)
Impact resistance and energy absorbing capability are of great interest in the design of composite sandwich structures. This paper experimentally studies damage, failure and energy absorption properties of foam core sandwich panels with aluminum and glass fiber reinforced plastic (GFRP) facesheets subjected to low velocity impact. Tests are performed using a drop weight impact tower at different impact velocities. The energy absorbing capabilities of aluminum and composite facesheet sandwich panels with PUR and PS foam core are evaluated by means of absorbed energy-time histories and by specific parameters as normalized absorbed energy, specific energy absorption, and crush force efficiency. Stiffer panels behave better at lower impact velocities, while more ductile ones do better if impact energy is increased.
Keywords: Low velocity impact; Sandwich panels; Skin and core damage; Energy absorption parameters